Antioxidants Vitamin C and Vitamin E for the Prevention and Treatment of Cancer (Blackwell Science Inc, 2006)
Many writers have suggested that the adequacy of vitamin supply to cells and tissues influences the development, progress, and outcome of cancer. In this article, we report data from a systematic review of studies testing the impact of antioxidants vitamins C and E to prevent and treat cancer. The results show there is no statistical evidence from the existing studies that the vitamins beneficially affect survival or prevent new tumors. Some studies showed clinically significant results but lacked statistical power and should be repeated with larger samples of patients.